Electrochemical Oxidation of Polyalcohols in Alkaline Media on Palladium Catalysts Promoted by the Addition of Copper. (10th November 2016) - Muneeb, Omar; Estrada, Jose; Tran, Lyndon; Nguyen, Kelly; Flores, Jennifer; Hu, Shuozhen; Fry-Petit, Allyson M.; Scudiero, Louis; Ha, Su; Haan, John L.
Highlights: Glycerol oxidation rate increases by 14-fold on PdCu catalyst Polyalcohol oxidation rate increases by 3-14 times on all PdCu catalysts d-band center shifts on all PdCu catalysts Abstract: Pd-Cu catalysts (Pd63 Cu37 /C, Pd46 Cu54 /C, Pd28 Cu72 /C, Pd11 Cu89 /C) and Pd/C were synthesized, characterized, and used to electrochemically oxidize ethylene glycol (EG), propylene glycol (PG), and glycerol (G). The oxidation rate at −0.4 V vs SCE after 3 hours on each PdCu/C catalyst was compared Pd/C. The oxidation rate for every polyalcohol on every PdCu/C catalyst was at least 3 times greater than on the Pd/C catalyst. The greatest promotion for the oxidation of EG was observed on Pd28 Cu72 /C (7 times faster), for PG was on Pd11 Cu89 /C (12 times), and for G was on Pd63 Cu37 /C (14 times). We observe a decrease in density of states near the Fermi level with increasing amount of Cu and a shift of the d-band center away from the Fermi energy. This surface electronic perturbation could be one of the factors affecting the oxidation of the polyalcohols. A second factor could be the bi-functional effect as we also observe an increase in hydroxyl adsorption at lower potentials on all PdCu/C compared to Pd/C. Therefore, we suggest that the combination of both of these effects, electronic and bifunctional, contributes to the promotion of the oxidation of these polyalcohols. Furthermore, the ratio of Cu to Pd appears to play an important role in the oxidation rate.